(untitled) (Bangladesh Veterinarian, 2025)
This study was carried out in the Rangpur Division, Bangladesh, to identify domestic cat breeds and assess their reproductive performance. Data were obtained through direct questionnaire administered to cat owners, complemented by regular observation of breed characteristics, behaviour, and reproductive traits. Ten breeds were identified: Indigenous, Persian, Persian (Calico), Maine Coon, Bengal Cat, Mixed, British Shorthair, Turkish Angora, Scottish Fold and American Shorthair. Common oestrus signs included vocalization, rolling, rubbing of the body and genital area, affectionate behaviour, and receptivity to male. The age at sexual maturity among females ranged from 6 to 23 months, with Persian cats exhibiting the highest mean age at maturity (16.2 ± 3.8 months, P<0.05). Oestrus cycle length varied from 7 to 45 days, with Bengal cats having the longest cycle (25.5 ± 6.4 days, P<0.05). Indigenous cats generally matured in spring and summer, although some showed year-round oestrus when housed with tomcats. Gestation lasted 57 – 67 days, with no significant difference between breeds; the longest was recorded in Scottish Folds (64.2 ± 2.4 days). Litter sizes ranged from 2 to 10 kittens, with Bengal cats producing the largest average litters (6.0 ± 3.5 kitten). Postpartum oestrus began 30–90 days after parturition. Pregnancy rates were highest in Indigenous cats (86.1%) and lowest in Scottish Folds (77.8%). Abortion rates were highest in Scottish Folds (28.6%) and lowest in Indigenous cats (16.1%). The sex ratio of kittens was approximately 49 males to 50 females. Kitten mortality was highest in Persian cats (21.8%) and lowest in American Shorthairs (11.8%). These findings provide valuable insights into breed-specific reproductive physiology, which can support breeding management strategies and inform veterinary reproductive care. Bang. vet. 2025. Vol. 42, No. 1 – 2, 17 – 27